2015
DOI: 10.3354/aei00126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic introgression of farmed salmon in native populations: quantifying the relative influence of population size and frequency of escapees

Abstract: Farmed escapees may threaten the genetic integrity of native salmon populations through interbreeding. However, introgression requires survival until maturation, successful reproduction and successful early development. These traits are often compromised in domesticated animals selected for high performance in captivity. This makes it difficult to predict introgression levels in native populations. A recent study estimated genetic introgression of farmed escaped Atlantic salmon Salmo salar in 20 Norwegian rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Moreover, associations between the incidence of escaped farmed salmon in rivers, and 352 river-specific estimates of temporal genetic change (Glover et al 2012) and admixture 353 (Glover et al 2013;Heino et al 2015;Karlsson et al 2016) prevented an in-depth region-wide analysis of aquaculture production in this study.…”
mentioning
confidence: 76%
“…Moreover, associations between the incidence of escaped farmed salmon in rivers, and 352 river-specific estimates of temporal genetic change (Glover et al 2012) and admixture 353 (Glover et al 2013;Heino et al 2015;Karlsson et al 2016) prevented an in-depth region-wide analysis of aquaculture production in this study.…”
mentioning
confidence: 76%
“…4) suggesting that smaller salmon populations are at greater risk of hybridization and introgression with escaped domestic individuals as noted in Norway 34,38 . This relationship is consistent with the dilution of domestic individuals in larger wild populations, as well the consequences of increased competition between wild and domestic individuals both on the spawning grounds and at juvenile stages 26,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of cumulative introgression has been population-specific, and was not solely dependent on the frequency of escapees observed in the population. It has been suggested that such demographic processes in the native population as spawning success and survival of the offspring influence the relative success of farmed salmon in the wild (Heino et al, 2015). Hatchery released and native extirpated salmon populations were identified in Poland using an Atlantic salmon array (Pocwierz-Kotus et al, 2015;Bernas et al, 2016).…”
Section: Comparison Of Wild and Hatchery Stocks: Effects Of Escapeesmentioning
confidence: 99%